Pre-Service Teachers' Opinions on Teaching Thinking Skills - AKINOĞLU, ORHAN (ESKISEHIR OSMANGAZI UNIV, FAC EDUCATION, 2016)
The purpose of the present study is to determine pre-service teachers. opinions on teaching thinking skills. 134 senior pre-service pre-school, English and mathematics teachers studying at a state university in Istanbul participated in the study which is designed based on survey model. A questionnaire which was developed by the researchers was used in data collection and percentage and frequency values were calculated for the data analysis. The results showed that pre-service teachers thought that thinking skills could be taught and teaching thinking skills should begin in pre-school level. They regarded the mixed approach as the most effective approach in teaching thinking skills. They considered that teachers. and administrators. modeling were considerably important in thinking-friendly classrooms and schools. They believed that being open to different opinions was the most important attribute of teachers who promote thinking. Pre-service teachers perceive themselves partially competent in developing students. thinking skills in the future. However, they emphasized the need for training in teaching thinking skills at schools.
Keywords: thinking skills; curriculum and instruction; teaching thinking skills; critical thinking; creative thinking; HIGHER-ORDER THINKING; PROBLEM-SOLVING SKILLS; STUDENTS; EDUCATION; INSTRUCTION; CLASSROOM